RTID-06. TRENDS IN INTERNATIONAL INVESTMENT IN CHILDHOOD, ADOLESCENT AND YOUNG ADULT (CYA) BRAIN TUMOR RESEARCH 2006-2018, WITH A FOCUS ON DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (12th November 2021) - Davies, Lynne; Weinstein, Amy
Abstract: Organizations funding brain tumor research want to identify gap areas for funding individually or in collaboration and want to better understand existing project focus to maximize new project investments. The International Cancer Research Partnership and the US Coalition Against Childhood Cancer used international research portfolio data to assess the landscape of CYA brain tumor research. From 2006-2018, investment for brain tumor research increased from 13m to 73m, and as a percentage of the CYA portfolio, brain tumor research received the highest percent investment (30%) in 2018. Research into treatment had risen (from 6m to 38m) as had research into biology (from 3m to 19m) - an essential foundation for more future personalized treatments. Given the lifelong impact on survivors it was encouraging that survivorship research investment had also started to increase. While 5-year survival for CYA cancers is now over 80%, survival for Diffuse Intrinsic Pontine Glioma (DIPG) remains very low. To assess capacity for future progress, several indicators were considered. The number of new DIPG projects per year increased from an average of 3 per year (2006-2012) to 11 (2013-2018) and funding increased from 0.5m (2006) to 10m (2018). Also, by 2018, 9 projects included a training component to build future research capacity. The number of laboratories researching DIPG increased from 2 in the US (2006) to 53 institutions in 6 countries (2018). Recent years had seen increased funding for pre-clinical models essential for identifying new targets. Collaborative initiatives such as DIPG-Open and DIPG-All had been funded to collect biological samples and accelerate translation of therapeutics to the clinic. Despite evidence that 5-year survival had improved from 1% to 2%, clearly major advances need to be made in new treatments, and monitoring the funding landscape carefully to make strategic investments will be essential.